(a) Solve the separable equation
"\\frac{d y(x)}{d x}+4 x y(x)=8x :"
Solve for "\\frac{d y(x)}{d x} :" :
"\\frac{d y(x)}{d x}=-4(-2 x+x y(x))" Simplify:
"\\frac{d y(x)}{d x}=x(-4 y(x)+8)"
Divide both sides by "-4 y(x)+8:"
"\\frac{\\frac{d y(x)}{d x}}{-4 y(x)+8}=x"
Integrate both sides with respect to "\\boldsymbol{x}:"
"\\int \\frac{\\frac{d y(x)}{d x}}{-4 y(x)+8} d x= \\int x d x"
Evaluating this integrals:
"-\\frac{1}{4} \\log (-4 y(x)+8)=\\frac{x^{2}}{2}+c_{1}" where "c_{1}" is an arbitrary constant
Solve for "y(x):"
"y(x)=-\\frac{1}{4} e^{-2\\left(x^{2}+2 c_{1}\\right)}+2" By simplifying the arbitrary constants, we have:
"y(x)=-\\frac{1}{4} e^{-2\\left(x^{2}+c_{1}\\right)}+2"
(b)
"(6xy+2y^2-5)dx+(3x^2+4xy-6)dy=0 \\qquad y(1)=2" The given differential equation is of the form:
"Mdx + Ndy =0" With:
"M = 6xy+2y^2-5 \\text{ and } N= 3x^2+4xy-6" We proceed to check the exactness of the two equations. For exactness,
"\\frac{\\partial M}{\\partial y}=\\frac{\\partial N}{\\partial x}" Thus:
"\\frac{\\partial M}{\\partial y}=6x+4y=\\frac{\\partial N}{\\partial x}" We then proceed to solve the equation.
"\\Phi_x = \\int(6xy+2y^2-5)dx = 3x^2y+2xy^2-5x\\\\\n\\Phi_y= \\int (3x^2+4xy-6)dy= 3x^2y+2xy^2-6y" The general solution of the DE is:
"3x^2y+2xy^2-5x-6y=c" Evaluating the general solution using the IVP "y(1)=2" :
"3(1)^2(2)+2(1)(2)^2-5(1)-6(2)=c\\\\\n6+8-5-12=c\\\\\n\\therefore c=-3" Thus the solution is:
"3x^2y+2xy^2-5x-6y=-3"
Comments
Leave a comment